Disposal of Waste From Cementing Operation Offshore Oil and Gas Wells Building - Campos, Letícia Ferraço de; Paiva, Pedro Mello; Rodrigues, Pedro Paulo Gomes Watts; Ferreira, Maria Inês Paes; Lugon Junior, Jader (Ciência e Natura, 2017)
This paper presents computer modeling applied to the disposal simulation residual volume from offshore cementing unit, where the cement paste used by cementing operations of oil and gas wells. The software used was MOHID WATER with a lagrangian approach where the solid part of the residue was represented by conservative particles. It is able to assess the behavior of the solid part of the residue in the water column and its accommodation on the seabed. Future works using the Life Cycle Impact Assessment (LCIA) standard methods are considered to understand the results and the possible resulting harm to marine organisms.